Prevalence and Assessment of Malnutrition Risk among Hospitalized Children in Romania - Mărginean, Oana (International Centre for Diarrhoeal Disease Research, Bangladesh, 2014)
Malnutrition is a prevalent condition in hospitalized children. Our aims were to evaluate the nutritional state and to validate the STRONGkids risk assessment tool in a hospitalized paediatric population in Romania. This is a prospective single-centre study in a tertiary teaching hospital in Romania (May 2011-January 2012). We calculated the STRONGkids score and measured the children's height and weight. Standard deviation <-2 for weight-for-height and height-for-age was considered to indicate acute or chronic malnutrition respectively. Two hundred seventy-one children were included, with median age of 5.2 years and median hospital stay of 2.01 days. Prevalence of malnutrition and severe malnutrition was 37% and 15% respectively. Using the STRONGkids screening tool, 58% of the children were found at risk of malnutrition (24% were at high risk). The kappa coefficient of agreement between STRONGkids and WHO malnutrition classification was 0.61. When a low serum protein level was used in upgrading STRONGkids risk category, kappa increased significantly to 0.71 (p=0.001). A modified STRONGkids score, incorporating total serum protein levels, performs well in predicting malnutrition in hospitalized paediatric population in Romania.